Case Report: Controversies in managing pulmonary enteric adenocarcinoma: reflections from an early-stage case - Bao, Yuchen; Liu, Dongdong; Wang, Yanzhe; Wu, Zhigang; Wang, Haitao (Frontiers in Oncology, 2025)
Pulmonary enteric adenocarcinoma (PEAC) is a rare non-small cell lung cancer subtype characterized by predominant intestinal differentiation (≥50%) and histological resemblance to colorectal adenocarcinoma. We report a 70-year-old male ex-smoker with an incidentally detected 18×11 mm spiculated lung nodule on chest CT, which subsequently demonstrated intense FDG uptake (SUVmax 14.0) on PET-CT. Histopathological evaluation confirmed PEAC. Immunohistochemistry revealed HER2 overexpression (3+) and intestinal differentiation markers (CK7+, CK20+, CDX2+, Villin+), while molecular testing showed wild-type ERBB2 and no actionable mutations. The patient underwent successful R0 resection with no recurrence at 8-month follow-up. This case underscores the critical importance of a multimodal diagnostic approach integrating immunohistochemical markers (notably CK7’s superior specificity), PET-CT imaging, and endoscopic evaluation to reliably differentiate PEAC from metastatic gastrointestinal malignancies. Furthermore, the patient’s favorable outcome following R0 resection without adjuvant therapy reinforces surgical intervention as the cornerstone of treatment for localized PEAC, particularly in early-stage disease. Advanced cases require early multidisciplinary collaboration to develop individualized treatment.